The Beat, the Scene, the Sound: A DJ's Journey through the Rise, Fall, and Rebirth of House Music in New York City - DJ Disciple, DJ Disciple; Kronk, Henry (Rowman & Littlefield Publishers, 2023)
A thrilling and tumultuous, behind-the-scenes account of house music in NYC. The Beat, the Scene, the Sound follows DJ Disciple and his behind-the-scenes account of how DJs, promoters, fans, and others transformed house music from a DIY project into an international sensation—dive into the glitzy clubs, underground parties, and the diverse communities who made up the scene amidst the tumult of 1980s/90s-era NYC—between the fall of disco and the rise of EDM. The book unearths many untold stories of the era. When house first rose to prominence in the 1980s, it brought people together—Palladium, Paradise Garage, Tunnel, Zanzibar, Studio 54, and other clubs were going strong. But as DJ Disciple established himself in the scene, he witnessed it shatter. During the crack-cocaine epidemic, he literally dodged bullets bringing his records to and from clubs at night. HIV/AIDS and homophobia threw up fear-based partitions. Then, mayors worked to close the clubs. House music was pushed underground and then abroad to the UK and Europe. Disciple and many other DJs sought to regain a footing in the United States, but that only became possible with the rise of commercialized EDM. With dozens of interviews and historic photographs, The Beat, the Scene, the Sound shows what is possible when you bring people together and what can unravel when you split them apart.